Predicting Gag, Discomfort, and Laryngeal Visualization in Patients Undergoing Flexible Laryngoscopy with Stroboscopy. (February 2022) - Kiessling, Patrick; Bayan, Semirra; Lohse, Christine; Orbelo, Diana
Objective: To investigate potential associations between the Predictive Gagging Survey (PGS) with patient experience of gag and discomfort as well as provider perception of patient gag and level of laryngeal visualization during flexible laryngoscopy with stroboscopy (FL-S). Methods: A total of 53 adult patients undergoing FL-S were recruited for this prospective non-controlled study. PGS was completed before FL-S. Patients rated perceived level of gag and discomfort on a 10-point severity scale after FL-S. Additionally, providers completed a Gagging Severity Index (GSI) reflecting their impression of patient gag and level of laryngeal visualization following FL-S. Spearman rank correlation coefficients were used to assess associations. Results: There was a positive association with PGS score and patient perception of gagging (0.34; P  = .013) and patient perception of discomfort (0.38; P  = .005). No significant association was found between PGS score and provider GSI (−0.12; P  = .39) or level of laryngeal visualization (0.15; P  = .29). A negative association was found between level of laryngeal visualization and patient perception of gagging (−0.34; P  = .012) and discomfort (−0.44; P  = .001). No significant differences were found between current and former smokers compared to never smokers for GSI or patient-perceived gag or discomfort. Conclusions: While not predictive of GSI or level of laryngeal visualization, the PGS was found to be a useful tool in predicting patient experience of gagging and discomfort during FL-S, further reinforcing the subjective experience of this procedure. Use of the PGS may be helpful in identifying specific candidates who may struggle with subjective discomfort or gagging during FL-S for future studies considering interventions to manage and meaningfully decrease discomfort. Having such an instrument is important given the low number of individuals who struggle with discomfort during the exam.